A red fluorophore comprising a borinate-containing xanthene analogue as a polyol sensor. Issue 42 (5th October 2016) - Shimomura, N.; Egawa, Y.; Miki, R.; Fujihara, T.; Ishimaru, Y.; Seki, T.
Abstract : A xanthene derivative containing a borinate centre emitted red fluorescence. Sugars induced a spectral change through modification of the LUMO and catechol quenched the fluorescence by PET. Abstract : A xanthene derivative containing a borinate moiety emitted red fluorescence with a high quantum yield. The interaction between the borinate and a sugar molecule induced a fluorescence change based on the change in the HOMO–LUMO gap. The response was pH-resistant in a wide range. In addition, catechol quenched through photoinduced electron transfer. The red fluorescence and polyol binding ability of dyes will pave the way for new biological applications of chemical sensors.